COMPARATIVE STUDY OF HISTORICAL PLACE NAMES IN UZBEK AND ENGLISH LANGUAGE - Jo’raqulova Hurmatoy; Madalov Navruz (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: There are names of places which can be translated and which are not according to the differences of affixes and letters in many languages. This article explores the orthographic and phonetic differences between the names of historical places in English and Uzbek. This article is demonstrated by Uzbek toponym examples.